The brave bunny - Daniels, Lucy; Ellis, Andy (Hodder Children's London, 2001)
Laura Baker's bunny Nibbles likes Mandy a lot, but Laura's nosy cousin Tom makes him frightened. Later on that night, Nibbles must be very brave when he gets sick, and is taken to Animal Ark. Can Mr Hope find out what is wrong?